The cholesterol‐binding motif of the HIV‐1 glycoprotein gp41 regulates lateral sorting and oligomerization. (13th June 2014) - Schwarzer, Roland; Levental, Ilya; Gramatica, Andrea; Scolari, Silvia; Buschmann, Volker; Veit, Michael; Herrmann, Andreas
Summary Enveloped viruses often use membrane lipid rafts to assemble and bud, augment infection and spread efficiently. However, the molecular bases and functional consequences of the partitioning of viral glycoproteins into microdomains remain intriguing questions in virus biology. Here, we measured Foerster resonance energy transfer by fluorescence lifetime imaging microscopy (FLIM‐FRET) to study the role of distinct membrane proximal regions of the human immunodeficiency virus glycoprotein gp41 for lipid raft partitioning in living Chinese hamster ovary cells (CHO‐K1). Gp41 was labelled with a fluorescent protein at the exoplasmic face of the membrane, preventing any interference of the fluorophore with the proposed role of the transmembrane and cytoplasmic domains in lateral organization of gp41. Raft localization was deduced from interaction with an established raft marker, a fluorescently tagged glycophosphatidylinositol anchor and the cholesterol recognition amino acid consensus (CRAC) was identified as the crucial lateral sorting determinant in CHO‐K1 cells. Interestingly, the raft association of gp41 indicates a substantial cell‐to‐cell heterogeneity of the plasma membrane microdomains. In complementary fluorescence polarization microscopy, a distinct CRAC requirement was found for the oligomerization of the gp41 variants. Our data provide further insight into the molecular basis and biological implications of the cholesterol dependent lateral sorting of viral glycoproteins for virus assembly at cellular membranes.